O jogo mestre da matéria e energia como instrumento de ensino e aprendizagem em física - Sousa, Helanderson Santos de (2022)
This dissertation aims to explain how the use of games, when applied in a thoughtful, planned and correct way, has the ability to provide a more pleasurable, motivating, exciting, active and, therefore, more efficient physics learning, eminently in what is refers to elementary school, a stage of basic education in which play and games are still very present and important in the school environment and beyond. The new National Common Curriculum Base (BNCC) has brought changes to the primary school curriculum, according to the current curriculum, students now have contact with physics-related subjects since the sixth year. Therefore, the use of didactic games, games and games, appear as a resource for a differentiated and fun class, which can serve as an instrument for a more active and engaging methodology which provides significant learning and directly impact on the multiple intelligences of students and on their interpersonal interactions. Based on authors who corroborate this thesis, we developed a didactic game, the Master of Matter and Energy (MME) - name that refers to the thematic unit that is more related to the teaching of physics in the new BNCC -, which was developed to be applied in classes from the eighth grade of elementary school. The MME is a board and card game that can be used as a previous organizer, as an instrument for fixing subjects worked in the classroom, or even as an assessment instrument, in order to provide the physics or science teacher with an alternative to make its most interesting, active and profitable classes, with the main objective of a deeper learning by the students, without leaving aside the fun.